Pengaruh Media Audio Visual Dalam Meningkatkan Hasil Menulis Teks Berita Pada Siswa SMA Negeri 11 Makassar - Feby Wahyuni; Hasriani; Christy (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2026)
This study aims to determine how audiovisual media is applied to improve news text writing. This research was conducted at SMA Negeri 11 Makassar. The problem of this research is how the results of writing news texts. Implementation, improvement, activity and student response in writing news text using audiovisual media. This type of research is quantitative. The form of pre-experimental design research with one group pre-test post-test design. The population of the study was all students of class XI. The research sample was taken using purposive sampling technique, so that class XI 7 with a total of 30 people was obtained as the experimental class. The results of the study showed that the learning outcomes of writing news texts were a post-test score of 12.63 and a pre-test score of 9.83. From the data, the N-Gain calculation was carried out at 0.54 with a moderate category, meaning that there was an increase in the ability to write news texts using audiovisual media. The implementation results reached a value of 94.45 with a very good category. The average data on student activities showed negative behavior of 6.13% and positive behavior of 93.84%. Student response data showed that the use of audiovisual media showed a positive response of 88.74% and a negative 11.25%.